Criminalization of Abuse of Authority in Indonesia: A Lesson from Beschikking in the Field of Taxation - ZM, Syehabudin (Journal of Tax Law and Policy, 2024)
Cases of criminalization of policy and/or criminalisation of office that are still ongoing in Indonesia are still a matter of debate among the law. It is concluded that a policy and/or beschikking has also occurred in the tax sector, so it is necessary to conduct a study or jurisprudence normative on the formulation of the problem questioning how the legal construction of a beschiking in the field of taxation can be punishable for abuse of authority. It is determined that a beschikkings in the area of taxations can be penalized for abuses of authorities if on such beschikkingen has passed the test of abuse authority to PTUN and / or there has been sufficient initial evidence that on such Beschikking there are elements of acts against the law (monetary) that cause damage to the financial or the economy of the State. (misalnya, pemerasan, korupsi, atau penyuapan). It is recommended that the Tax Authority have an ideal policy in dealing with the challenges of criminalization of beschikking, both in the case of pre- and post-criminalization against a beschiking.